2020
DOI: 10.1097/inf.0000000000002504
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent Influenza Vaccine Prevents Illness and Reduces Healthcare Utilization Across Diverse Geographic Regions During Five Influenza Seasons

Abstract: Background: We evaluated an inactivated quadrivalent influenza vaccine (IIV4) in children 6–35 months of age in a phase III, observer-blind trial. Methods: The aim of this analysis was to estimate vaccine efficacy (VE) in preventing laboratory-confirmed influenza in each of 5 independent seasonal cohorts (2011−2014), as well as vaccine impact on healthcare utilization in 3 study regions (Europe/Mediterranean, Asia-Pacific and Central America). Healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 130 publications
0
11
0
1
Order By: Relevance
“…As Kenya formulates its influenza vaccination policy, the choice of broad immunity ( Epstein 2018 ) or more valence vaccines (e.g. quadrivalent regimen, Dbaibo et al. 2019 ) should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As Kenya formulates its influenza vaccination policy, the choice of broad immunity ( Epstein 2018 ) or more valence vaccines (e.g. quadrivalent regimen, Dbaibo et al. 2019 ) should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… Ref. ORV HICs versus LMICs IgA titres to ORV fourfold lower in infants from LMICs + No; review of multiple different studies Yes 12 ORV HICs versus LMICs Meta-analysis of RCTs of ORV: vaccine efficacy in HICs 94% (after 12 months) compared with 44% in LMICs + No; meta-analysis Yes 13 Oral cholera vaccine Sweden versus Nicaragua Mean IgA titres to CTB 1.6–1.9-fold lower in children in Nicaragua than in children in Sweden; vibriocidal antibody concentrations also much higher in children in Sweden + Yes Yes 14 OPV HICs versus LMICs ~100% of individuals in HICs seroconvert following OPV compared with ~70% in LMICs + No; review of multiple different studies No 15 Oral Shigella vaccine (candidate) USA versus Bangladesh High levels of immunogenicity in adults in the USA but little or no immunogenicity in infants in Bangladesh + No No 16 DTP–HepB–Hib vaccine HICs versus Indonesia Similar levels of immunogenicity for infants in HICs and in Indonesia = No Yes 17 Quadrivalent influenza vaccine Europe/Mediterranean, Asia-Pacific and Central America Higher efficacy in children from HICs (73.4%) with lowest efficacy in LMICs (30.3%) + Yes Yes, but some vaccine strain differences in different regions 18 RTS,S (malaria vaccine) Burkina Faso, Ghana, Gabon, Kenya, Tanzania, Malawi and Mozambique Efficacy after 3 doses ranges from 40% to 77% at 11 different trial sites across 7 African countries NA Yes Yes 19 YF-17D vaccine Switzerland versus Uganda Antigen-specific T cell and neutraliz...…”
Section: Suboptimal Vaccine Responses In Lmicsmentioning
confidence: 99%
“…However, a growing number of studies suggest that responses to other licensed and candidate parenteral vaccines could be impaired in individuals from LMICs (Table 1 ). For example, a recent phase III trial to evaluate the efficacy of an inactivated quadrivalent influenza vaccine over five influenza seasons in children in three geographically diverse regions found that there was a higher level of vaccine efficacy in cohorts from countries with higher socioeconomic status 18 . The efficacy of the RTS,S malaria vaccine after three doses has been observed to vary from 40% to 77% at 11 trial sites across 7 African countries 19 , which suggests that vaccine immunogenicity may also vary at a more geographically localized level.…”
Section: Suboptimal Vaccine Responses In Lmicsmentioning
confidence: 99%
“…Broadly, influenza vaccines come in two forms: trivalent (containing antigens of influenza A subtypes H1N1 and H3N2, and one of the two influenza B subtypes) or quadrivalent (containing strains of H1N1, H3N2 and both Victoria and Yamagata influenza lineages). Quadrivalent vaccines have been shown to reduce morbidity, mortality and healthcare service usage, compared to trivalent vaccination [24,25]. The quadrivalent vaccine has been found to demonstrate an incremental cost-effectiveness ratio of £27 378 per quality-adjusted life-year versus nonvaccination [26,27].…”
Section: Influenza Vaccine Design and Deliverymentioning
confidence: 99%